Innovative Approaches to Attracting Investment for the Economic Development of Small Communities - Popov, Mykola; Mazur, Hennadii; Mukhin, Oleksii; Artemchuk, Mykyta; Babichev, Anatoliy (International Journal of Economics and Financial Issues, 2025)
The aim of the research is to assess the effectiveness of innovative approaches to attracting investment in the regions of Ukraine, taking into account the impact of digitalization, structural reforms and PPPs. The study is based on multiple linear regression using panel data for 20 regions of Ukraine (2019–2023), ordinary least squares (OLS) estimation and fixed effects. The analysis showed that digitalization (β = 0.47, p = 0.001), PPP (β = 0.50, p = 0.000), and public spending (β = 0.45, p = 0.000) are the most effective mechanisms for attracting investment. At the same time, the unemployment rate (β = -0.40, p = 0.000) is negatively correlated with investment activity. The largest investment volumes are concentrated in Kyiv, Lviv, and Odesa, while the smallest are in Chernihiv, Zakarpattia, and Volyn regions. Innovative approaches that combine digital technologies, PPP and structural economic reforms are more effective in attracting investment compared to traditional methods. Further analysis should focus on developing a comprehensive model for assessing the effectiveness of digital platforms, artificial intelligence, and algorithmic financial mechanisms for attracting investment in small communities.